Inflammasome Sensor Nlrp1b-Dependent Resistance to Anthrax Is Mediated by Caspase-1, IL-1 Signaling and Neutrophil Recruitment - Moayeri, Mahtab (Public Library of Science, 2010)
Bacillus anthracis infects hosts as a spore, germinates, and disseminates in its vegetative form. Production of anthrax lethal and edema toxins following bacterial outgrowth results in host death. Macrophages of inbred mouse strains are either sensitive or resistant to lethal toxin depending on whether they express the lethal toxin responsive or non-responsive alleles of the inflammasome sensor Nlrp1b (Nlrp1b(S/S) or Nlrp1b(R/R), respectively). In this study, Nlrp1b was shown to affect mouse susceptibility to infection. Inbred and congenic mice harboring macrophage-sensitizing Nlrp1b(S/S) alleles (which allow activation of caspase-1 and IL-1β release in response to anthrax lethal toxin challenge) effectively controlled bacterial growth and dissemination when compared to mice having Nlrp1b(R/R) alleles (which cannot activate caspase-1 in response to toxin). Nlrp1b(S)-mediated resistance to infection was not dependent on the route of infection and was observed when bacteria were introduced by either subcutaneous or intravenous routes. Resistance did not occur through alterations in spore germination, as vegetative bacteria were also killed in Nlrp1b(S/S) mice. Resistance to infection required the actions of both caspase-1 and IL-1β as Nlrp1b(S/S) mice deleted of caspase-1 or the IL-1 receptor, or treated with the Il-1 receptor antagonist anakinra, were sensitized to infection. Comparison of circulating neutrophil levels and IL-1β responses in Nlrp1b(S/S),Nlrp1b(R/) (R) and IL-1 receptor knockout mice implicated Nlrp1b and IL-1 signaling in control of neutrophil responses to anthrax infection. Neutrophil depletion experiments verified the importance of this cell type in resistance to B. anthracis infection. These data confirm an inverse relationship between murine macrophage sensitivity to lethal toxin and mouse susceptibility to spore infection, and establish roles for Nlrp1b(S), caspase-1, and IL-1β in countering anthrax infection.